Elizabethkingia meningoseptica and Contact Lens Use - Beato, Joao (2016)
A 47-year-old man presented to our emergency department complaining of acute ocular pain and redness of his left eye. Ophthalmological antecedents included use of semi-rigid contact lens and primary open-angle glaucoma. Slit-lamp examination revealed a small central corneal ulcer associated with stromal inflammatory infiltrate. Scraping from the corneal ulcer was positive for Elizabethkingia meningoseptica. He was empirically treated with topical 0.5% levofloxacin and 0.3% gentamicin, and five weeks later the infection had resolved. In this case report we describe the uncommon association between contact lens and Elizabethkingia meningoseptica. Despite possible serious complications associated with this atypical agent, prompt diagnosis and adequate treatment lead to good visual prognosis.